Vegetable fiber-containing composite resin molding having aroma sustained release property

JP2025024079AActive Publication Date: 2025-02-19PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024197956
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-19
Estimated Expiration
2040-10-28

AI Technical Summary

Benefits of technology

【0009】 本発明に係る複合樹脂成形体は、植物繊維に芳香成分を含有する植物繊維、主剤樹脂に結晶性樹脂を使用し、50質量%以上90質量%以下の高濃度で植物繊維を含有するため、植物繊維周囲の結晶化度と樹脂全体の結晶化度が高く、植物繊維から揮発される芳香成分の放出速度が抑制される。そのため、この複合樹脂成形体は長期間の芳香徐放性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024079000001_ABST
    Figure 2025024079000001_ABST
Patent Text Reader

Abstract

To provide a composite resin molding having aroma sustained release properties for a long period of time without depending on a surrounding environmental condition.SOLUTION: A vegetable fiber-containing composite resin molding having aroma sustained release properties includes a main agent resin, vegetable fibers, and dispersant. The vegetable fibers contain aroma components. The main agent resin comprises a crystalline resin. The content of the vegetable fibers is 50-90 mass% when the total amount of the main agent resin, the vegetable fibers and the dispersant is 100 mass%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plant fiber-containing composite resin molding having sustained fragrance release properties. [Background technology]

[0002] So-called "general-purpose plastics" such as polyethylene (PE) and polypropylene (PP) are relatively inexpensive, lightweight (a fraction of the weight of metals or ceramics), and easy to process, such as by molding. For this reason, general-purpose plastics are used as materials for a variety of everyday items such as bags, various types of packaging, various containers, and sheets, as well as industrial parts such as automobile parts and electrical parts, and daily necessities and miscellaneous goods.

[0003] In recent years, sensory characteristics are required as added value in addition to basic performance for everyday products such as daily necessities and lifestyle products that use resins, and for exterior parts such as home appliance casings and automobile interior and exterior parts. Examples of sensory characteristics include texture and feel such as touch, color, and scent. In particular, scents are suitable for adding to familiar products because they have mood-improving and relaxation effects. Methods for adding scent include carrying or incorporating aromatic components in resins.

[0004] On the other hand, even if the fragrance is good, if there is a large amount of it, it will be unpleasant. Therefore, it is necessary to release an appropriate amount of fragrance. In addition, since the fragrance is caused by the aromatic component, which is a volatile component, it is difficult to maintain the effect of the fragrance for a long period of time, that is, to impart the ability to release the fragrance sustained. Therefore, simply supporting or containing the aromatic component in the resin makes it impossible to control the amount and release speed of the aromatic component, which may result in unpleasant sensation or the fragrance not being sustained for a long period of time. In Patent Document 1, the aromatic component is supported on a composite resin containing cellulose particles, thereby allowing an appropriate amount of the aromatic component to be released sustained for a long period of time. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-201811 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the composite resin described in Patent Document 1, the release rate of the aromatic component is controlled only by the repetition rate of moisture absorption and drying (respiration rate) of the cellulose particles in the composite resin, so the release rate varies greatly depending on the surrounding environmental conditions. Therefore, there is a problem that the aromatic sustained release can be maintained stably for a long period of time only under specific environments. Another problem is that a separate process of supporting the aromatic component on the composite resin is required.

[0007] The present invention is intended to solve the above-mentioned problems in the conventional art, and has an object to provide a composite resin molding that has a sustained fragrance release property for a long period of time, independent of the surrounding environmental conditions. [Means for solving the problem]

[0008] The composite resin molding according to the present invention includes a base resin, a plant fiber, and a dispersant, The plant fiber contains an aromatic component, The base resin is a crystalline resin, When the total amount of the base resin, the plant fibers, and the dispersant is taken as 100% by mass, the content of the plant fibers is 50% by mass or more and 90% by mass or less. Effect of the Invention

[0009] The composite resin molding according to the present invention uses plant fibers containing aromatic components as the plant fibers and a crystalline resin as the main resin, and contains plant fibers at a high concentration of 50% by mass to 90% by mass, so that the crystallinity around the plant fibers and the crystallinity of the entire resin are high, and the release rate of the aromatic components volatilized from the plant fibers is suppressed. Therefore, this composite resin molding has a long-term sustained release of aromatic components. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic diagram showing a configuration of a plant fiber-containing composite resin molded body according to a first embodiment. FIG. [Diagram 2] 3 is a schematic diagram showing the orientation and crystalline state of vegetable fibers in a skin layer and a core layer of the composite resin molding according to the first embodiment. FIG. [Figure 3A] FIG. 2 is a diagram showing conditions in Examples 1 to 8 and Comparative Examples 1 to 4. [Figure 3B] FIG. 1 is a diagram showing the measurement results in Examples 1 to 8 and Comparative Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The composite resin molding according to the first aspect includes a base resin, a plant fiber, and a dispersant, The plant fiber contains an aromatic component, The base resin is a crystalline resin, When the total amount of the base resin, the plant fibers, and the dispersant is taken as 100% by mass, the content of the plant fibers is 50% by mass or more and 90% by mass or less.

[0012] A composite resin molding according to a second aspect is the composite resin molding according to claim 1, wherein in the first aspect, the plant fibers have an average particle size of 1 μm or more and 3 mm or less.

[0013] A composite resin molded product according to a third aspect may be the composite resin molded product according to the first or second aspect, wherein the base resin has a crystallinity of 30% or more.

[0014] The composite resin molding of the fourth aspect may be any one of the first to third aspects above, wherein the crystallinity of the base resin around the plant fiber in the composite resin molding is 1.05 times or more compared to the area containing only the base resin.

[0015] The composite resin molding of the fifth aspect may be any one of the first to fourth aspects, wherein in the particle size distribution of the plant fiber, the particle size variation Δd expressed as Δd=d90 / d10, where d90 is a particle size at or below which 90% of the particles have a numerical value and d10 is a particle size at or below which 10% of the particles have a numerical value, is 6 or more.

[0016] The composite resin molding of the sixth aspect may be any one of the first to fifth aspects above, wherein the fiber length direction of the plant fibers in the skin layer of the composite resin molding is oriented at an angle of 0° or more and 30° or less with respect to the surface of the composite resin molding.

[0017] A composite resin molding according to a seventh aspect is any one of the first to sixth aspects, wherein a skin layer on the surface of the composite resin molding has a thickness of 600 μm or less.

[0018] Hereinafter, a plant fiber-containing composite resin molded article according to an embodiment will be described with reference to the drawings. In the following description, the same components are denoted by the same reference numerals, and the description will be omitted as appropriate.

[0019] (Embodiment 1) Fig. 1 is a schematic diagram showing the configuration of a plant fiber-containing composite resin molding 10 according to embodiment 1. Fig. 2 is a schematic diagram showing the orientation and crystalline state of plant fibers in a skin layer and a core layer of the composite resin molding 10 according to embodiment 1. The composite resin molded body 10 according to the first embodiment is composed of a base resin 1 composed of a matrix of a non-crystalline portion 11 and a crystalline portion 12, a plant fiber 2, an aromatic component 3, and a dispersant 4. As shown in FIG. 1, the composite resin molded body 10 has the plant fiber 2, the aromatic component 3, and the dispersant 4 dispersed in the matrix of the base resin 1, and the aromatic component 3 is present inside the plant fiber 2 and in the matrix of the base resin 1, and the dispersant 4 is present at the interface between the plant fiber 2 and the base resin 1. As shown in FIG. 2, the composite resin molded body is roughly divided into two layers, a skin layer 13 on the surface and a core layer 14 on the inside. When the molten resin enters the mold during molding, the resin surface in contact with the mold surface is rapidly cooled, and the rest of the resin inside is slowly cooled. Since the cooling speed differs between the surface and the inside, the characteristics such as the crystallinity are different, and it is possible to distinguish the skin layer from the core layer by microscopic observation or the like. In this specification, the layer on the surface of the molded body that is rapidly cooled during molding is defined as the skin layer, and the layer inside the molded body that is slowly cooled during molding is defined as the core layer. According to this composite resin molded body 10, for example, plant fibers 2 containing aromatic components and crystalline main resin 1 are used, and the plant fibers 2 are contained at a high concentration of 50% by mass or more and 90% by mass or less, so that the crystallinity around the plant fibers 2 and the crystallinity of the entire resin are high, and the release rate of the aromatic components 3 volatilized from the plant fibers 2 is suppressed. Therefore, this composite resin molded body 10 has a long-term fragrance sustained release property.

[0020] The members constituting this composite resin molded body 10 will be described below.

[0021] <Main resin> The base resin 1 in the embodiment is preferably a crystalline resin in order to suppress the release of volatile components, and more preferably a thermoplastic resin in order to ensure good moldability. Examples of crystalline resins include olefin resins (including cyclic olefin resins), polyamide resins, polyphenylene ether resins (polymers of 2,6-xylenol, etc.), crystalline polyester resins, halogen-containing resins, and liquid crystal polymer resins. The above resins may be used alone or in combination of two or more kinds. The base resin is not limited to the above materials as long as it has crystallinity. In addition, when two or more kinds of resins are used, it is sufficient that at least one of the resins has crystallinity.

[0022] Of these crystalline resins, the main resin is preferably an olefin resin having a relatively low melting point. The olefin resin includes homopolymers of olefin monomers, copolymers of olefin monomers, and copolymers of olefin monomers and other copolymerizable monomers. Examples of the olefin monomer include linear olefins (α-C2-20 olefins such as ethylene, propylene, 1-butene, isobutene, 1-pentene, 4-methyl-1-pentene, and 1-octene), and cyclic olefins. These olefin monomers may be used alone or in combination of two or more. Of the above olefin monomers, linear olefins such as ethylene and propylene are preferred. Specific examples of olefin resins include copolymers of linear olefins (particularly α-C2-4 olefins) such as polyethylene (low density, medium density, high density, or linear low density polyethylene, etc.), polypropylene, ethylene-propylene copolymers, and terpolymers such as ethylene-propylene-butene-1.

[0023] The base resin 1 is preferably a crystalline resin. The crystalline portion has a denser structure than the amorphous portion. Therefore, the diffusion speed of liquids and gases is significantly slower in the crystalline portion than in the amorphous portion. Since the aromatic components diffuse in the composite resin molding as gas or liquid components, the diffusion speed is significantly slower in the crystalline portion than in the amorphous portion. The presence of crystalline portions in the resin reduces the diffusion speed of the aromatic components, thereby enabling the release of the aromatic components from the composite resin molding to be maintained for a long period of time, that is, the aromatic components can be released gradually. Therefore, the base resin 1 is preferably a crystalline resin.

[0024] <Plant fiber> In the embodiment, the raw material of the plant fiber 2 may be natural materials such as pulp, wood (coniferous or broad-leaved), cotton linters, kenaf, Manila hemp (abaca), sisal, jute, sabai grass, esparto grass, bagasse, rice straw, wheat straw, wheat, reed, bamboo, and tea leaves. Waste plant materials discarded after commercial use such as sake barrels may also be used. Natural materials modified with functional monomers including acids, amines, and epoxy may also be used. The plant fiber 2 is preferably fibrous or particulate material obtained by pulverizing the above natural materials.

[0025] <Aromatic ingredients> The aromatic component 3 in the embodiment is preferably a component derived from a natural material or a component generated by the deterioration of a component derived from a natural material during the manufacturing process of the material, and more preferably has volatility. Examples of aromatic components include pinene, cadinol, and hinokiol. However, the aromatic component is not limited to the above components as long as it is a component contained in plant fibers.

[0026] <Dispersant> Examples of the dispersant 4 in the embodiment include various titanate-based coupling agents, silane coupling agents, unsaturated carboxylic acids, maleic acid, maleic anhydride, or modified polyolefins grafted with the anhydrides thereof, fatty acids, fatty acid metal salts, fatty acid esters, etc. The silane coupling agents are preferably unsaturated hydrocarbon-based or epoxy-based. The surface of the dispersant may be modified by treating it with a thermosetting or thermoplastic polymer component. The dispersant 4 is appropriately selected depending on the combination of the base resin 1 and the plant fiber 2.

[0027] The plant fiber 2 is preferably a plant fiber containing an aromatic component, and the aromatic component is preferably derived from the plant fiber. When using a plant fiber that does not contain an aromatic component, a separate process of supporting the aromatic component is required. For example, when supporting an aromatic component in a composite resin composition, a post-process such as immersing the composite resin composition in oil containing an aromatic component is required. In addition, since the plant fiber-containing composite resin molding has the texture of the plant fiber in its appearance, if the aromatic component is a component other than that derived from the plant fiber, there is a possibility that the appearance and scent will be incongruous and the functionality of the composite resin molding as a whole will be reduced. Therefore, the plant fiber is preferably a plant fiber containing an aromatic component, and the aromatic component is preferably derived from the plant fiber.

[0028] The total amount of the base resin 1, the plant fibers 2, and the dispersant 4 in the composite resin molded body is 100 mass %. The aromatic component 3 is contained in the plant fibers 2, and is therefore included in the amount of the plant fibers 2.

[0029] The content of plant fibers in the composite resin molding is preferably 50% by mass or more and 90% by mass or less, and more preferably 55% by mass or more and 75% by mass or less, from the viewpoints of increasing the content of aromatic components and the crystallization degree of the main resin.

[0030] As shown in FIG. 1, the composite resin molding is composed of a base resin 1, plant fibers 2, aromatic components 3, and a dispersant 4. The base resin 1 functions as a matrix, and the plant fibers 2, aromatic components 3, and dispersant 4 are dispersed in the base resin. In the composite resin molding, the plant fibers 2 not only serve as a release source for the aromatic components 3, but also function as a crystal nucleating agent, thereby improving the crystallinity of the base resin. Because the plant fibers 2 function as a crystal nucleating agent, the proportion of crystalline parts present around the plant fibers 2 is high. In other words, the composite resin molding has a pseudo core-shell structure in which the plant fibers 2 can be regarded as the core and the crystalline parts as the shell structure. This structure significantly suppresses the diffusion speed of the aromatic components 3 from inside the plant fibers 2 to the base resin 1.

[0031] If the content of plant fibers is less than 50%, the total amount of aromatic components is small, and the sustained release of aromatic components cannot be maintained for a long period of time. In addition, the crystallinity of the entire main resin is low, and the effect of suppressing the diffusion rate of aromatic components is reduced. If the content of plant fibers is 90% or more, the content of the main resin is too small compared to the content of plant fibers, so that the plant fibers 2 cannot be encapsulated in the main resin 1, and a large amount of the plant fibers 2 is exposed on the surface of the main resin, and the release of the aromatic components 3 cannot be suppressed. In addition, the content of the main resin is too small, so that the fluidity of the composite resin composition is significantly reduced, and kneading and injection molding cannot be stably performed. Therefore, the content of plant fibers in the composite resin molding is preferably within the above range.

[0032] The average particle size of the plant fibers 2 is preferably 1 μm or more and 3 mm or less, and more preferably 20 μm or more and 1 mm or less. If the average particle size is smaller than 1 μm, the size of the plant fibers is small, so the amount of aromatic components retained per fiber is small. In addition, the surface area per fiber is very large, so it is not possible to add the plant fibers to the base resin at a high concentration. If the average particle size is larger than 3 mm, the plant fibers cannot be uniformly dispersed in the base resin, and the sustained release of the aromatic components in the composite resin molding varies within the composite resin molding. Therefore, it is preferable that the average particle size of the plant fibers 2 is within the above range.

[0033] The crystallinity of the base resin 1 is preferably 30% or more, and more preferably 60% or more. If the crystallinity of the base resin 1 is less than 30%, the proportion of non-crystalline parts is high, so that the diffusion speed of the aromatic components cannot be suppressed very much, and the composite resin molding cannot have long-term sustained release properties. Therefore, the crystallinity of the base resin 1 is preferably within the above range.

[0034] The degree of crystallinity of the base resin 1 around the plant fibers in the composite resin molded product is preferably 1.05 times or more, and more preferably 1.10 times or more, compared to the portion containing only the base resin 1. If the crystallinity of the base resin around the plant fibers is less than 1.05 times that of the portion containing only the base resin, the crystallinity of the base resin around the plant fibers is so low that a pseudo core-shell structure cannot be formed by the plant fibers and the resin around them. In other words, the aromatic components cannot be trapped within the plant fibers, and the release rate cannot be suppressed. Therefore, it is preferable that the crystallinity of the base resin 1 around the plant fibers in the composite resin molding is within the above range compared to the portion containing only the base resin 1.

[0035] The particle size variation of the plant fibers 2 is preferably Δd≧6, and more preferably Δd≧8. In this specification, Δd is an index representing the particle size variation. Δd is the value obtained by dividing the d90 value of the particle size distribution by d10, and is defined by the following formula. Δd=d90 / d10 Here, d90 is the particle size at which the proportion of particles below this value in the particle size distribution is 90%, and d10 is the particle size at which the proportion of particles below this value in the particle size distribution is 10%.

[0036] Since the amount of aromatic components contained in the plant fibers varies depending on the size, the release rate of the aromatic components varies depending on the fiber size. When the particle size variation is Δd<6, the variation in the plant fibers is small, so the release rate of the aromatic components from the plant fibers becomes constant and the sustained release property decreases. Therefore, it is preferable that the particle size variation of the plant fibers 2 is Δd≧6.

[0037] It is preferable that the fiber length direction of the plant fibers 2 in the skin layer of the composite resin molding is oriented at an angle of 0° or more and 30° or less with respect to the composite resin surface. The ends of the plant fibers 2 in the fiber length direction are particularly defibrated in the fiber surface due to kneading during the production of the composite resin molding. Compared to the non-defibrated parts, the defibrated parts have a larger surface area and release aromatic components faster. If the fiber length direction of the plant fibers in the surface skin layer is oriented at an angle of more than 30° with respect to the skin layer, the release of aromatic components in the skin layer direction becomes faster, and the sustained release of aromatic components decreases. Therefore, it is preferable that the fiber length direction of the plant fibers 2 in the skin layer is oriented at an angle in the above range with respect to the surface of the composite resin molding.

[0038] The thickness of the skin layer on the surface of the composite resin molded product is preferably 600 μm or less. When molding by injection molding, the molten resin is injected into a mold, and the surface portion in contact with the mold is rapidly cooled to form the skin layer. Meanwhile, the internal core layer is formed while being slowly cooled. Since crystals grow by being slowly cooled, the skin layer formed by rapid cooling has a low degree of crystallinity, and the core layer formed by slow cooling has a high degree of crystallinity. If the thickness of the skin layer is greater than 600 μm, the proportion of the skin layer portion with a low degree of crystallinity increases, so the release rate of the aromatic component cannot be suppressed, and the sustained release of the aromatic component decreases. Therefore, the thickness of the skin layer on the surface of the composite resin molded product is preferably within the above range.

[0039] As the kneading device used in the manufacturing method of the composite resin molded body, a kneader, a Banbury mixer, an extruder, and a roll kneader are preferable. Among them, it is more preferable to use a twin-screw kneader and a roll kneader. Note that the kneading device is not limited to the above devices as long as it has a rotor as a kneading means. In addition, since the aromatic components contained in the plant fibers are volatile components, it is preferable to knead them at as low a temperature as possible. EXAMPLES

[0040] FIG. 3A shows the conditions for Examples 1 to 8 and Comparative Examples 1 to 4, and FIG. 3B shows the measurement results for Examples 1 to 8 and Comparative Examples 1 to 4.

[0041] Example 1 A plant fiber-containing composite resin composition was produced by the following production method. As described above, a kneader, a Banbury mixer, an extruder, a roll kneader, or the like can be used as the kneading device, but a twin-screw kneader is used in the examples.

[0042] Polypropylene was used as the base resin, hinoki cypress powder as the plant fiber, which had an average particle size of 50 μm and a particle size variation Δd of 6, was crushed in a grinder, and maleic anhydride-modified polypropylene was used as a dispersant.These were weighed out in a mass ratio of 43:55:2 and dry-blended.

[0043] The dry-blended raw materials were fed to the kneader at 2 kg / h by a weight feeder. As mentioned above, a twin-screw kneader (JSW TEX30a, Inc.) was used as the kneader. The screw was of medium shear type. The composite resin discharged from the twin-screw kneader was hot-cut to produce composite resin pellets containing plant fibers.

[0044] The prepared plant fiber-containing composite resin pellets were used to prepare test pieces of composite resin moldings using an injection molding machine (180AD manufactured by Japan Steel Works). The conditions for preparing the test pieces were resin temperature 200°C, mold temperature 40°C, injection speed 60mm / s, and holding pressure 80MPa. The pellets were fed into the screw of the molding machine through a hopper, and the penetration at that time was measured by the pellet loss amount per hour, and it was confirmed that it was constant. The shape of the test piece was changed depending on the evaluation items described below, and a dumbbell test piece of size 1 was prepared for measuring the elastic modulus, and a cup test piece was prepared for the sensory evaluation of the fragrance and the sustained release evaluation. The obtained test pieces of the plant fiber-containing composite resin moldings were evaluated by the following method.

[0045] [Evaluation items for composite resin molded products] (Aroma sensory evaluation) Using the resulting cup-shaped test piece, a sensory evaluation test for the scent (aroma sensory evaluation) was conducted. The test subjects were asked to actually smell the scent and rate the pleasantness of the scent of the test piece on a 7-point scale from 1 to 7 (1=very unpleasant, 2=unpleasant, 3=slightly unpleasant, 4=normal, 5=slightly pleasant, 6=pleasant, 7=very pleasant), and the strength of the scent on a 7-point scale from 1 to 7 (1=very weak, 2=weak, 3=slightly weak, 4=just right, 5=slightly strong, 6=strong, 7=very strong). In the sensory evaluation method of the fragrance, fragrance pleasantness was rated as × for 1-4, △ for 5, ○ for 6, and ◎ for 7. Fragrance strength was rated as × for 1-2 and 6-7, △ for 3 and 5, and ○ for 4. Fragrance pleasantness rated × had a sensory evaluation result of × regardless of the fragrance strength. Fragrance pleasantness rated △ and strength rated × had an evaluation result of ×, and strength rated △ or ○ had an evaluation result of △. Fragrance pleasantness rated ○ and strength rated × had an evaluation result of ×, strength rated △ had an evaluation result of △, and strength rated ○ had an evaluation result of ○. Fragrance pleasantness rated ◎ and strength rated × had an evaluation result of ×, strength rated △ had an evaluation result of ○, and strength rated ○ had an evaluation result of ◎. The test piece of Example 1 was rated as having a pleasant scent of 6 and a strong scent of 4, resulting in an evaluation of ◯.

[0046] (Fragrance sustained release evaluation) Using the resulting cup-shaped test piece, a test was conducted to evaluate the sustained release of fragrance (sustained release of fragrance). Normally, the test pieces are left at room temperature, but to conduct accelerated testing, they were placed in a small hot air dryer at 60°C, and the fragrance strength of the sample was evaluated every 24 hours. Testing in an environment where hot air at 60°C is blown is an accelerated test about 50 times faster than testing in a normal atmosphere at room temperature. After 90 hours or more, fragrance strength ratings of 1-2 and 6-7 were rated as ×, 3 and 5 were rated as △, and 4 was rated as ○. The test piece was rated 4, which was rated as ◯. The test piece with a fragrance intensity of 4 after 120 hours or more was rated as ⊚.

[0047] (Elastic modulus of composite resin molding) Tensile tests were carried out using the obtained No. 1 dumbbell-shaped test pieces. Here, the elastic modulus was evaluated as follows: values ​​less than 1.9 GPa were marked x, values ​​between 1.9 GPa and 2.7 GPa were marked △, values ​​between 2.7 GPa and 3.6 GPa were marked ○, and values ​​equal to or greater than 3.6 GPa were marked ◎. The elastic modulus of the test piece was 4.2 GPa and was rated as excellent.

[0048] (Crystallization degree of composite resin molding) (Crystallization degree of composite resin) The melting (crystallization) peak was measured by differential scanning calorimetry (DSC) and the heat of fusion was calculated. The crystallinity was calculated by the following formula. Crystallinity = (measured heat of fusion / heat of fusion of perfect crystal) x 100 Here, the crystallinity was evaluated as follows: less than 30% was marked x, 30% or more but less than 60% was marked ◯, and 60% or more was marked ⊚. The composite resin molding had a crystallinity of 53% and was evaluated as excellent.

[0049] (Crystallization around the fiber) A portion was cut out from the No. 1 dumbbell-shaped test piece obtained and observed by Raman spectroscopy. Those in which the degree of crystallinity of the resin around the plant fiber was less than 1.05 times the degree of crystallinity of the crystalline portion alone were marked with an X, and those in which it was 1.05 times or more were marked with an O. The crystallinity of the resin around the plant fibers of the test piece was 1.12 times that of the part containing only crystals, and was evaluated as good.

[0050] (skin layer fiber orientation) A portion was cut out from the obtained No. 1 dumbbell-shaped test piece, and a polarizing microscope measurement of the cross section was performed. On the obtained polarizing microscope measurement image, the angle of the fiber length direction of the plant fiber in the skin layer was measured with the test piece surface set at 0°. If the angle of the fiber length direction of the plant fiber was 70° or more, it was marked as ×, if it was 30° or less and less than 70°, it was marked as △, and if it was 0° or more and less than 30°, it was marked as ○. The angle of the plant fibers in the skin layer of the test piece in the fiber length direction was 10°, and the test piece was evaluated as good.

[0051] (Skin layer thickness) A part was cut out from the obtained No. 1 dumbbell-shaped test piece and subjected to polarizing microscope measurement. The thickness of the skin layer was measured on the obtained polarizing microscope image. If the thickness of the skin layer was greater than 600 μm, it was marked as ×, and if it was 600 μm or less, it was marked as ○. The thickness of the skin layer of this test piece was 430 μm, and the evaluation was good.

[0052] Example 2 In Example 2, the amount of plant fiber was increased, and the weight ratio of the base resin:plant fiber:dispersant was changed to 27:70:3. Other conditions were the same as in Example 1 to prepare a plant fiber-containing composite resin pellet and a molded body. Evaluations were also performed in the same manner as in Example 1.

[0053] Example 3 In Example 3, fibers with an average particle size of 1 mm were used as the vegetable fibers, which were larger than those in Example 1. The other material conditions and process conditions were the same as in Example 1 to produce cellulose fiber-containing composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0054] Example 4 In Example 4, the injection molding conditions were changed to a higher mold temperature during injection molding compared to Example 1. Regarding other material conditions and process conditions, cellulose fiber-containing composite resin pellets and molded bodies were produced in the same manner as in Example 1. Evaluations were also performed in the same manner as in Example 1.

[0055] Example 5 In Example 5, vegetable fibers with a fiber particle size variation Δd of 10 were used, which is larger than that in Example 1. The other material conditions and process conditions were the same as in Example 1 to produce cellulose fiber-containing composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0056] Example 6 In Example 6, plant fibers with a particle size variation of Δd=2 were used, which is smaller than that in Example 1, and other material conditions and process conditions were the same as in Example 1 to produce plant fiber-containing composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0057] Example 7 In Example 7, the injection molding conditions were changed to a higher resin temperature and a faster injection speed during injection molding compared to Example 1. The other material conditions and process conditions were the same as in Example 1 to produce cellulose fiber-containing composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0058] Example 8 In Example 8, the resin temperature during injection molding was lowered and the injection speed was slowed down compared to Example 1. Other material conditions and process conditions were the same as in Example 1 to produce a composite resin pellet containing vegetable fiber and a molded body. Evaluations were also performed in the same manner as in Example 1.

[0059] Comparative Example 1 In Comparative Example 1, pulp that had been bleached for a sufficiently long time and from which most of the residual components such as lignin and hemicellulose had been removed was used as the plant fiber, and the other material conditions and process conditions were the same as in Example 1 to produce composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0060] Comparative Example 2 In Comparative Example 2, polystyrene (PS), which is a non-crystalline resin, was used as the main resin, and the other material conditions and process conditions were the same as in Example 1 to prepare cellulose fiber-containing composite resin pellets and molded bodies. Evaluations were also performed in the same manner as in Example 1.

[0061] Comparative Example 3 In Comparative Example 3, the amount of plant fiber was reduced compared to Example 1, and the weight ratio of the base resin:plant fiber:dispersant was changed to 89:10:1. Other material conditions and process conditions were the same as in Example 1 to produce a plant fiber-containing composite resin pellet and a molded body. Evaluations were also performed in the same manner as in Example 1.

[0062] Comparative Example 4 In Comparative Example 4, the amount of plant fiber was increased compared to Example 1, and the weight ratio of the base resin:plant fiber:dispersant was changed to 2.5:95:2.5. Other material conditions and process conditions were the same as in Example 1 to produce a plant fiber-containing composite resin pellet and a molded body. Evaluations were also performed in the same manner as in Example 1.

[0063] The measurement results for each of Examples 1 to 8 and Comparative Examples 1 to 4 are shown in the table of FIG. 3B.

[0064] In Example 2, in which the amount of plant fiber was increased, the elastic modulus was 5.1 GPa because the fiber reinforcement effect of the plant fiber was greater than that of Example 1. The degree of crystallinity increased to 63% due to the increase in the amount of plant fiber. In addition, the amount of aromatic components increased due to the increase in the amount of plant fiber, and the aroma sensory evaluation result was ○, and the sustained release evaluation result was ○.

[0065] In Example 3, which used fibers with an average particle size of 1 mm, the fiber size was larger than in Example 1, and the amount of aromatic component contained inside each fiber increased, resulting in improved sustained release, and the aroma sustained release was rated as excellent.

[0066] In Example 4, in which the mold temperature during injection molding was set high, the composite resin was cooled more slowly than in Example 1, so the crystallinity increased to 64%, and the sustained fragrance release was evaluated as excellent.

[0067] In Example 5, which used plant fibers with a fiber particle size variation Δd = 10, the amount of aromatic components contained changed depending on the size of the fibers, and therefore the release period of the aromatic components from fibers of each size differed, improving the sustained release of the aromatic compound, and the evaluation result was rated as excellent.

[0068] In Example 6, which used plant fibers with a fiber particle size variation Δd=2, the fibers were approximately the same size and the release period of the aromatic components was also approximately the same, so the evaluation result for sustained aromatic release was Δ.

[0069] In Example 7, in which the resin temperature during injection molding was increased and the injection speed was increased, the skin layer was thinner than in Example 1 and the core layer was correspondingly larger, resulting in a slower release rate of the aromatic components and an evaluation of sustained release of ⊚.

[0070] In Example 8, in which the resin temperature during injection molding was low and the injection speed was slow, the skin layer was thicker than in Example 1, and the proportion of the core layer in the total resin was accordingly smaller. As a result, the release of the aromatic components could not be suppressed, and the sustained release property was evaluated as △. From the above, Examples 2, 3, 4, 5 and 7 achieved results equal to or better than Example 1 in all tests.

[0071] In Comparative Example 1, which used pulp from which most of the remaining components such as lignin and hemicellulose were removed as plant fibers, there was almost no aromatic component present, and as a result, the pleasantness of the aroma was rated 5 and the strength of the aroma was rated 1 in the aroma sensory evaluation, resulting in an evaluation result of x.

[0072] In Comparative Example 2, in which polystyrene (PS), a non-crystalline resin, was used as the main resin, the release rate of the aromatic components could not be controlled due to the absence of crystalline components in the resin, and the sustained release evaluation result was poor.

[0073] In Comparative Example 3, in which the weight ratio of plant fibers to the total raw materials was reduced, the amount of cellulose fibers was small, so the degree of crystallinity was low and the total amount of aromatic components was small, resulting in a result of the aroma sensory evaluation of ×. In addition, the fiber reinforcement effect on the composite resin was small, and the elastic modulus was 2.0 GPa.

[0074] In Comparative Example 4, in which the weight ratio of plant fiber to the total raw materials was increased, the amount of fiber was so large that the viscosity became too high, which increased the load on the device and made it impossible to knead and mold stably. Therefore, test pieces could not be produced and evaluation was not possible.

[0075] From the above evaluation, when a non-crystalline resin was used, the long-term sustained release property was decreased. When the plant fiber concentration was low, the amount of aromatic components was decreased and the fragrance was insufficient. When the plant fiber concentration was too high, stable kneading and molding were not possible. From the above, it was found that by using plant fibers containing aromatic components and crystalline resins, and by setting the plant fiber content to between 50% and 90% by mass, composite resin moldings can be produced stably, have high mechanical strength, and have long-term sustained fragrance release properties.

[0076] In addition, the present disclosure includes appropriate combinations of any of the various embodiments and / or examples described above, and can achieve the effects of each embodiment and / or example. [Industrial Applicability]

[0077] The composite resin molded article according to the present invention has mechanical strength superior to that of conventional general-purpose resins, and has sensual properties such as color, texture, and fragrance derived from plant materials, and can provide a molded article having a long-term sustained release of fragrance. The composite resin molded article according to the present invention can provide a long-term sustained release property that is not easily affected by the environment, so that a relaxation effect can be imparted to daily necessities, etc. Furthermore, since it has excellent mechanical strength, it can be used for home appliance housings, building materials, and automobile parts. [Explanation of symbols]

[0078] 1. Base resin 2. Plant Fiber 3 Aromatic ingredients 4. Dispersants 10 Composite resin molding 11 Amorphous part 12 Crystal Section 13 Skin Layer 14 Core Layer

Claims

1. The composition includes a base resin, vegetable fibers, and a dispersant, The plant fiber contains an aromatic component, The base resin is a crystalline resin, A composite resin molding, wherein the content of the plant fibers is 50% by mass or more and 90% by mass or less when the total amount of the base resin, the plant fibers, and the dispersant is 100% by mass.

2. 2. The composite resin molding according to claim 1, wherein the plant fibers have an average particle size of 1 μm or more and 3 mm or less.

3. 3. The composite resin molding according to claim 1, wherein the base resin has a crystallinity of 30% or more.

4. 4. The composite resin molding according to claim 1, wherein the degree of crystallinity of the base resin around the plant fiber in the composite resin molding is 1.05 times or more higher than that of a portion consisting of only the base resin.

5. 5. The composite resin molding according to claim 1, wherein in the particle size distribution of the plant fiber, the particle size variation Δd expressed as Δd = d90 / d10, where d90 is a particle size at which the ratio of particles below that value is 90% and d10 is a particle size at which the ratio of particles below that value is 10%, is 6 or more.

6. 6. The composite resin molding according to claim 1, wherein the fiber length direction of the plant fibers in the skin layer of the composite resin molding is oriented at an angle of 0° or more and 30° or less with respect to the surface of the composite resin molding.

7. 7. The composite resin molding according to claim 1, wherein a thickness of a skin layer on the surface of the composite resin molding is 600 [mu]m or less.

Citation Information

Patent Citations

  • Polyolefin resin composition containing organic natural filler

    JP1999012395A

  • Woody resin composition

    JP1999269316A

  • Antibacterial woody composite molding material and its manufacturing method

    JP2004058409A

  • Woody polyolefin resin composition

    JP2006036815A

  • Resin composition for molding

    JP2007045854A